Assessment of image processing techniques and ASTER SWIR data for the delineation of evaporates and carbonate outcrops along the Salt Lake Fault, Turkey. Issue 4 (16th February 2016) - Özyavaş, Aziz
ABSTRACT: The Advanced Spaceborne Thermal Emission and Reflection Radiometer (ASTER) multispectral sensor allows a variety of minerals to be diagnosed with the availability of six shortwave infrared (SWIR) bands. The study area located in a semi-arid region in central Turkey was flanked by the Salt Lake Fault in the west. ASTER SWIR bands and the adopted image processing techniques such as decorrelation stretch, band ratio, and feature-oriented principle component selection (FPCS) were applied for mapping both gypsum and carbonate rocks in the study area. Initially, the application of the decorrelation stretch method with a novel band combination successfully delineated the gypsum and carbonate outcrops. In addition to that, the principle component 4 (PC4) image obtained from the FPCS technique applied to a new band selection of ASTER data distinguished explicitly the carbonate outcrops. The resultant images, consistent with the geologic map of the study area, were compared with another and demonstrated that the gypsum and carbonate rocks were clearly identifiable. In addition to that, quantitative analyses of parallelepiped supervised classification images, band 9/band 8 ratio, and PC4 images in particular, yielded very compatible results.